FREE POWER-SEMICOMMUTATIVE TERNARY GROUPOIDS - Celakoska-Jordanova, Vesna; Celakoska, Emilija; Miovska, Valentina (Matematichki Bilten, 2018)
A description of free objects in the class \(P_sc\) of power-semicommutative ternary groupoids and a proper characterization of the class of free objects in \(P_sc\) by means of \(P_sc\)-injective ternary groupoids are obtained.